Useless and subversive: transmedia mobilization of Chilean students in social networks - Cardenas Neira, Camila (Romanica Olomucensia, 2014)
The students' mobilization cycle started in 2011 has made visible the Chilean youth in an unprecedented way in the postdictatorship history. Its political action has concerted the attention of the mass media that have turned the educational conflict into a polemic object of representation. In this context, the strategic use of internet and social networks has provided them with alternative routes for the development of resistant meanings. From the perspective of the Critical Discourse Studies, this article analyzes the communicative uses that construct a transmedia representation of the protesters from the "useless and subversive" designation widespread by the press after the mobilization of August 4. It is observed how the diffusion of multimodal discourses from some online environments to others affects the redefinition of the student's political action, unfolding a storytelling which models the youth identities from competitive forms of hetero and self-representation. It is concluded that, through intertextuality and successive recontextualization practices, the students subvert the dominant representations, adapting them to their favour. This implies that the semiotic production and transposition modifies social cognitions which are relevant for the resignification of the movement, whose effects are based on the performative character of its symbolic interactions.
Keywords: transmedia representation; Chilean students' movement; political action; multimodal discourses; online communication.